DETERMINATION OF MERCURY IN LIVER OF MARINE TETRAPODS BY COLD VAPOR ATOMIC FLUORESCENCE SPECTROMETRY AND INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY IN BIOLOGICAL SAMPLES: A SYSTEMATIC COMPARISON BETWEEN THE TWO TECHNIQUES - Silva, Raiza F. da [UNESP] (2021)
This study compares the techniques cold vapour atomic fluorescence spectrometry (CV-AFS) and inductively coupled plasma mass spectrometry (ICP-MS) for the determination of Hg in biological samples (hepatic tissue from marine tetrapods). Acid digestions were performed for the samples and aliquots of them were analysed by ICP-MS and CV-AFS. To minimize the Hg memory effect in its determination by ICP-MS, gold (200 mu g L-1 in 5% v v(-1) HCl) was added to the sample digests. The detection limits were 0.02 mg kg(-1) for ICP-MS and 0.01 mg kg(-1) for CV-AFS. Accuracy was assessed by the calculation of the recovery obtained from TORT-3 (lobster hepatopancreas) certified reference material analysis. Accurate results were obtained for both CV-AFS and ICP-MS. The comparison of the results obtained for hepatic tissue with and without lyophilization showed a significant difference among them (at 95% of confidence level), evidencing losses of Hg in the lyophilization process.